Heat-induced molten pool boundary softening behavior and its effect on tensile properties of laser additive manufactured aluminum alloy. (August 2018) - Dai, Donghua; Gu, Dongdong; Zhang, Han; Zhang, Jiayao; Du, Yuexin; Zhao, Tong; Hong, Chen; Gasser, Andres; Poprawe, Reinhart
Abstract: Changes in the microstructure and the mechanical properties of AlSi10 Mg alloy fabricated by selective laser melting combined with the subsequent heat treatment have been studied. The influence of the heat treatment on the molten pool boundary softening, microstructure evolution and the resultant mechanical properties has been elucidated. The as-fabricated specimens exhibited the various Si phase patterns within the different regions of the molten pool corresponding to the columnar perpendicular to the molten pool boundary and cellular columnar in the upper center region due to the various thermal behaviors. The solubility of Si atoms was decreased and rejected into fine Si particles with the formation of the molten pool boundary softening and the homogeneous distribution in the heat induced part, playing a key role in the mechanical properties of AlSi10 Mg alloy. The ultimate tensile strength decreased from 476.8 MPa for the as-fabricated part to 320.5 MPa while, the fracture ductility significantly increased from 7.33% to 13.3% as the test specimens were heat treated at 573 K for 2 h. It indicated that the microstructure evolution and tensile properties of the as-fabricated AlSi10 Mg alloy could be tailored through molten pool softening and size and morphology of the Si phase at the suitable heat treatments. Highlights: Molten pool boundary softening with homogeneous microstructure is obtained. Spherical pores with hydrogen expansion in heat treatment are found. Keyhole mode molten pool and the thermal behavior are discussed. Effect of molten pool boundary softening on fracture behavior is elucidated.